2011
DOI: 10.1242/jcs.092510
|View full text |Cite
|
Sign up to set email alerts
|

A feedback loop betweenWolbachiaand theDrosophila gurkenmRNP complex influencesWolbachiatiter

Abstract: SummaryAlthough much is known about interactions between bacterial endosymbionts and their hosts, little is known concerning the host factors that influence endosymbiont titer. Wolbachia endosymbionts are globally dispersed throughout most insect species and are the causative agent in filarial nematode-mediated disease. Our investigation indicates that gurken (grk), a host gene encoding a crucial axis determinant, has a cumulative, dosage-sensitive impact on Wolbachia growth and proliferation during Drosophila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 77 publications
(116 reference statements)
3
57
0
Order By: Relevance
“…In D. mauritiana, Wolbachia increases egg production by affecting the maintenance and division of germ-line stem cells [20], while in the wasp Asobara tabida , Wolbachia confers a reproductive advantage to the females by properly regulating apoptosis during oogenesis via its regulation of iron metabolism and ferritin expression [190,192]. However, in D. melanogaster highly infected females suffer from a range of oogenesis defects mediated via grk signalling [193]. Pararge aegeria females were also found to be infected with Wolbachia, but how this affects oogenesis in this species is at present not known.…”
Section: Discussionmentioning
confidence: 99%
“…In D. mauritiana, Wolbachia increases egg production by affecting the maintenance and division of germ-line stem cells [20], while in the wasp Asobara tabida , Wolbachia confers a reproductive advantage to the females by properly regulating apoptosis during oogenesis via its regulation of iron metabolism and ferritin expression [190,192]. However, in D. melanogaster highly infected females suffer from a range of oogenesis defects mediated via grk signalling [193]. Pararge aegeria females were also found to be infected with Wolbachia, but how this affects oogenesis in this species is at present not known.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi-knockdown of ColA causes loss of symbiont growth control resulting in disruption of the highly beneficial long-term relationship between host and symbiont (Login et al, 2011). Finally Serbus et al (2011) have demonstrated that Wolbachia -titer in D. melanogaster might be regulated through a feedback loop between the host gene gurken ( grk ) and the symbiont itself. Regarding our finding that Wolbachia -titers increase dramatically in the five Glossina hybrids compared to their non-hybrid mothers, we suggest that strict titer regulation of the symbiont is crucial in that system too.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that nutrient levels in the host cells play a key role in influencing titre while Wolbachia surface proteins that interact with specific host factors determine its localization. Support of this notion comes from the close association between Wolbachia and polarity determinants in the Drosophila oocyte (Serbus and Sullivan, 2007;Serbus et al, 2011).…”
Section: Factors Intrinsic To Wolbachia Influence Its Distribution Inmentioning
confidence: 98%